Unbirthday - Braswell, Liz (Los Angeles Disney Hyperion, 2020)
Returning to the place of nonsense from her childhood, Alice, now eighteen, tries to stop the Queen of Hearts' tyrannical rule before the End of Time, and save her own world as well as Wonderland.
Ages 12-18.
Grades 10-12.
114423
Keywords: Alice -- (Fictitious character from Carroll) -- Juvenile fiction; Queens -- Juvenile fiction; Imaginary places -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Fantasy; Young Adult Fiction -- Fairy Tales & Folklore -- Adaptations; Young Adult Fiction -- Action & Adventure -- General; Young Adult Fiction -- Fantasy -- General; Fantasy; Imaginary places; Imaginary wars and battles; Women; Geographical myths -- Juvenile fiction; Expeditions -- Juvenile fiction; Folklore; Kings and rulers -- Fiction; Fairy tales; Fantasy fiction; England; Young adult fiction; Fantasy fiction; Fairy tales; Young adult works; Juvenile works; Fiction